Model-independent reconstruction of the linear anisotropic stress [eta] - Pinho, Ana Marta; Casas, Santiago; Amendola, Luca (Arxiv, 2018)
In this work, we use recent data on the Hubble expansion rate $H(z)$, the quantity
Im Titel wird "eta" als griechischer Buchstabe dargestellt
Gesehen am 12.11.2020